2017
DOI: 10.1097/won.0000000000000357
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Experiences of Chinese Patients Living With an Ostomy

Abstract: The findings of this study demonstrate that patients with ostomy experience sexual dysfunction and many factors influence their quality of sexual life. WOC nurses and other healthcare providers should consider providing sexual health education for both the patient and spouse to improve the self-care capacity and quality of sexual life following ostomy surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 17 publications
2
12
0
2
Order By: Relevance
“…It may thus be prudent to refer these patients to professional counselling and training services about sexual health before and after stoma surgery. 10,11 Though incidence of suicidal tendencies amongst these patients is low; incidence of depression is considerably high up to 58.75% in our study. It is similar to findings in study by Anaraki et al 8 Depression causes direct negative impact on psychological domain of QOL in these patients.…”
Section: Discussionmentioning
confidence: 43%
“…It may thus be prudent to refer these patients to professional counselling and training services about sexual health before and after stoma surgery. 10,11 Though incidence of suicidal tendencies amongst these patients is low; incidence of depression is considerably high up to 58.75% in our study. It is similar to findings in study by Anaraki et al 8 Depression causes direct negative impact on psychological domain of QOL in these patients.…”
Section: Discussionmentioning
confidence: 43%
“…Traditionally, in order to ensure radical treatment, for ultra-low rectal cancer within 5 cm from the lower edge of the tumor to the anus, it is considered that combined abdominal and perineal resection (APR), that is, Miles surgery, is the standard treatment [1]. However, permanent stoma also brings more stoma-related complications [2] and urogenital dysfunction [3,4] to patients. In addition, long-term nursing care of stoma [5], persistent mental pressure of stoma on patient's image change, and other factors seriously affect the quality of life [6] and the realization of social function [7] of patients after Miles, making patients' attitude toward the postoperative treatment more negative.…”
Section: Introductionmentioning
confidence: 99%
“…This scale achieved good internal consistency, excellent test-retest reliability (two weeks, r = 0.80 and 0.89), and good construct validity. The Chinese version of the ASEX has been subsequently validated with different clinical samples, and was concluded that this version has high validity and reliability 28,29 .…”
Section: Methodsmentioning
confidence: 99%